A Novel Rat Model of Cardiac Donation After Circulatory Death Combined With Normothermic ex situ Heart Perfusion - Li, Jiale; Xue, Chuqing; Ling, Xiao; Xie, Yu; Pavan, Desai; Chen, Huimin; Peng, Qinbao; Lin, Shaoyan; Li, Kunsheng; Zheng, Shaoyi; Zhou, Pengyu (Frontiers in Cardiovascular Medicine, 2021)
Background: In heart transplantation, the adoption of hearts from donation after circulatory death (DCD) is considered to be a promising approach to expanding the donor pool. Normothermic ex situ heart perfusion (ESHP) is emerging as a novel preservation strategy for DCD hearts. Therefore, pre-clinical animal models of ESHP are essential to address some key issues before efficient clinical translation. We aim to develop a novel, reproducible, and economical rat model of DCD protocol combined with normothermic ESHP. Methods: Circulatory death of the anesthetized rats in the DCD group was declared when systolic blood pressure below 30 mmHg or asystole was observed after asphyxiation. Additional 15 minutes of standoff period was allowed to elapse. After perfusion of cold cardioplegia, the DCD hearts were excised and perfused with allogenic blood-based perfusate at constant flow for 90 minutes in the normothermic ESHP system. Functional assessment and blood gas analysis were performed every 30 minutes during ESHP. The alteration of DCD hearts submitted to different durations of ESHP (30, 60, and 90 minutes) in oxidative stress, apoptosis, tissue energy state, inflammatory response, histopathology, cell swelling, and myocardial infarction during ESHP was evaluated. Rats in the non-DCD group were treated similarly but not exposed to warm ischemia and preserved by the normothermic ESHP system for 90 minutes. Results: The DCD hearts showed compromised function at the beginning of ESHP and recovered over time, while non-DCD hearts presented better cardiac function during ESHP. The alteration of DCD hearts in oxidative stress, apoptosis, tissue energy state, histopathological changes, cell swelling, and inflammatory response didn’t differ among different durations of ESHP. At the end of 90-minute ESHP, DCD and non-DCD hearts presented similarly in apoptosis, oxidative stress, inflammatory response, myocardial infarction, and histopathological changes. Moreover, the DCD hearts had lower energy storage and more evident cell swelling compared to the non-DCD hearts. Conclusion: We established a reproducible, clinically relevant, and economical rat model of DCD protocol combined with normothermic ESHP, where the DCD hearts can maintain a stable state during 90-minute ESHP.